Deodorizing material and method for preparing the same
Patent Information
- Application Number
- CN202511362713.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-23
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-09-23
AI Technical Summary
本发明将吸附剂同光催化进行组合,既可以解决传统吸附剂在吸附饱和后需要更换的问题,又可弥补光催化剂吸附能力弱的短板,延长吸附剂的过滤寿命
[0034](1)本发明的催化层负载高活性二氧化钛,可将空气中的臭源进行催化分解,从而达到除臭效果,吸附层的金属氧化物兼顾除醛的同时也有优异的除臭性能;吸附层主要由活性炭与介孔金属氧化物组成,后者兼顾除醛与除臭:表面氨基可与甲醛反应生成碱,碱性基团能与甲硫醇反应生成稳定二硫键,产物均被活性炭吸附,助力空气净化。气态污染物通过过滤材料时,氨气等先经二氧化钛降解,减少异味和毒性,再经介孔金属氧化物后被活性炭吸附。此外,活性炭层的介孔二氧化锰反应放热,可降低二氧化钛催化所需能量,推动反应正向进行,提升恶臭物质去除效率。二者组合,延长过滤材料的使用寿命,长效去除空气中的恶臭气体。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of air purification technology, specifically to a deodorizing material and its preparation method. Background Technology
[0002] In recent years, with the improvement of people's living standards and health awareness, the demand for living environments has upgraded from single-function physical spaces to emotional containers that are healthy, multifunctional, personalized, and intelligent. While pursuing comfort, environmental health has also become a focus of close attention. The main sources of indoor odor pollutants include: volatile organic compounds emitted from household products or buildings, body odor, tobacco odor, aging odor, kitchen waste odor, and bathroom odor, etc.
[0003] Existing adsorption deodorizers on the market are mainly divided into two types according to their adsorption principles: physical deodorization and chemical deodorization. Physical deodorization uses porous materials (such as activated carbon / zeolite / alumina) to adsorb various odor sources in the air. Once adsorption equilibrium is reached, the adsorbent needs to be replaced. Chemical adsorption refers to the deodorizer reacting chemically with the odor source to remove it, thus specifically removing one or more odor sources. Currently, photocatalysis is also used for deodorization. Under a light source of a specific wavelength, the catalyst decomposes odor molecules, thus deodorizing them. However, photocatalysts have a low ability to capture odor source molecules and cannot efficiently and rapidly decompose them at low concentrations. Summary of the Invention
[0004] The purpose of this invention is to overcome at least one of the defects in the prior art by providing a deodorizing material and its preparation method. This invention utilizes composite filtration technology, combining adsorption and photocatalysis, to address indoor odor problems. By combining adsorbents with photocatalysis, this invention solves the problem of traditional adsorbents needing replacement after adsorption saturation, and also compensates for the weak adsorption capacity of photocatalysts, extending the filtration life of the adsorbent.
[0005] The objective of this invention can be achieved through the following technical solutions:
[0006] One of the objectives of this invention is to provide a deodorizing material, comprising a catalyst layer, a first hot melt adhesive layer, a core material, a second hot melt adhesive layer, an adsorption layer, a third hot melt adhesive layer, and a meltblown fabric layer stacked sequentially.
[0007] The catalyst layer is loaded with titanium dioxide; the adsorption layer is obtained by spreading adsorption particles, which are a mixture of activated carbon and mesoporous metal oxides loaded with active components.
[0008] Furthermore, the catalyst layer is prepared by mixing tetrabutyl titanate, ethanol, acetylacetone, water, and nitric acid to obtain an impregnation solution; then immersing a copper mesh in the impregnation solution, removing it, drying it, and calcining it to obtain the catalyst layer.
[0009] Further, the molar ratio of tetrabutyl titanate, ethanol, acetylacetone, water, and nitric acid is 1:(10-40):(0.1-1.0):(0.5-2):(0.05-0.2).
[0010] Furthermore, during impregnation, the copper mesh is impregnated at a rate of at least 10 cm / min, and this process is repeated multiple times to increase the thickness of the impregnation solution coating on the copper mesh.
[0011] Furthermore, during drying, the drying temperature is 40-70℃, and the drying time is 5-15 minutes;
[0012] Furthermore, during calcination, the calcination temperature is 450-600℃, and the calcination time is 0.5-1.5h.
[0013] Furthermore, the adsorbent particles are prepared by impregnating mesoporous metal oxide with an equal volume of active components using an ultrasonic method, and then mixing it evenly with activated carbon to obtain adsorbent particles.
[0014] Furthermore, the mesoporous metal oxide is one or more of manganese, titanium, zinc, and copper;
[0015] Furthermore, the active component is highly active manganese dioxide;
[0016] Furthermore, the activated carbon has a specific surface area of 1300-1600 m². 2 Microporous coconut shell activated carbon with a particle size of 0.18-0.25mm (60-80 mesh) and an iodine value of 1000-1500mg / g;
[0017] Furthermore, the mass ratio of the mesoporous metal oxide, the active component, and the activated carbon is (25-35):1:(80-120).
[0018] Furthermore, the preparation method of the highly active manganese dioxide is as follows: mesoporous manganese dioxide is placed in an ethanol solution, the pH is adjusted to acidic by a pH adjuster, and after being dispersed evenly, aminomethyltrimethoxysilane (CAS:18166-02-4) is added, and the solution is heated in a water bath until it completely disappears to obtain highly active manganese dioxide;
[0019] The ethanol solution is an ethanol solution with a volume fraction of 85%.
[0020] The pH adjuster is nitric acid with a mass fraction of 30%.
[0021] The dispersion was achieved by ultrasonic water bath dispersion at an ultrasonic frequency of 40 kHz and a temperature of 45 ℃.
[0022] The mass ratio of mesoporous manganese dioxide to amino-containing trimethoxysilane is 30:1;
[0023] The water bath heating temperature is 60℃.
[0024] Furthermore, the bone material has a weight of 40-50 g / m³. 2 Polyester (PET) nonwoven fabric;
[0025] Furthermore, the basis weight of the first and third hot melt adhesive layers is 10-15 g / m³. 2 ;
[0026] Furthermore, the first hot melt adhesive layer and the third hot melt adhesive layer are hot melt adhesive webs composed of one or more of polyolefin (PO), copolyester (PES), and polyamide (PA), and the melting range of the hot melt adhesive webs is 80-120°C;
[0027] Furthermore, the second hot melt adhesive layer has a basis weight of 18-25 g / m². 2 The copolyester (PES) hot melt adhesive mesh has a melting temperature range of 80-120℃.
[0028] The second objective of this invention is a method for preparing the deodorizing material as described above, comprising the following steps:
[0029] The copper mesh, the first hot melt adhesive layer, and the skeleton are stacked on the workbench in sequence. After the first hot pressing to fix them, the second hot melt adhesive layer, the adsorption layer, and the third hot melt adhesive layer are stacked in sequence. After the second hot pressing to fix them, meltblown cloth is stacked on the third hot melt adhesive layer to obtain the deodorizing material.
[0030] The adsorption layer is formed by uniformly spreading adsorption particles, with a particle spreading amount of 180-200 g / m³. 2 .
[0031] Furthermore, a desktop conveyor is provided below the copper mesh, with a transmission frequency set to 15-20Hz.
[0032] Furthermore, a high-voltage electrostatic powder sprinkler is installed above the copper mesh, with the powder amount adjustable within a range of 25%-35%.
[0033] Compared with the prior art, the present invention has the following advantages:
[0034] (1) The catalyst layer of this invention is loaded with highly active titanium dioxide, which can catalytically decompose odor sources in the air, thereby achieving a deodorizing effect. The metal oxide of the adsorption layer has excellent deodorizing performance while also removing formaldehyde. The adsorption layer is mainly composed of activated carbon and mesoporous metal oxide, the latter of which has both formaldehyde removal and deodorizing effects: the surface amino groups can react with formaldehyde to generate alkali, and the basic groups can react with methanethiol to generate stable disulfide bonds. All products are adsorbed by activated carbon, which helps to purify the air. When gaseous pollutants pass through the filter material, ammonia and other gases are first degraded by titanium dioxide, reducing odor and toxicity, and then adsorbed by activated carbon after passing through the mesoporous metal oxide. In addition, the mesoporous manganese dioxide in the activated carbon layer reacts exothermically, which can reduce the energy required for titanium dioxide catalysis, promote the reaction to proceed in the forward direction, and improve the removal efficiency of odorous substances. The combination of the two extends the service life of the filter material and effectively removes odorous gases from the air for a long time.
[0035] (2) The deodorizing material catalyst layer of the present invention is supported by copper mesh, which ensures catalytic efficiency while maintaining good rigidity of the filter under high air volume, thereby reducing the structural resistance of the material and thus reducing the filtration resistance.
[0036] (3) The middle layer of the deodorizing material of the present invention is made of PES hot melt adhesive mesh with high rigidity and high toughness. The PES adhesive mesh can maintain stable mechanical properties while being hot-pressed and formed, and has excellent strength and rigidity. It enhances the rigidity of the deodorizing material and also allows the activated carbon layer to have certain gaps, which can increase the effective contact area between the gas and the activated carbon layer, and can also reduce the filtration resistance of the deodorizing material to a certain extent. Detailed Implementation
[0037] The present invention will now be described in detail with reference to specific embodiments. These embodiments are implemented based on the technical solution of the present invention, providing detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0038] Example 1
[0039] To address the shortcomings of existing photocatalysts, such as their low ability to capture odor source molecules and their inability to efficiently and rapidly decompose odor source substances at low concentrations, this embodiment provides a method for preparing a multi-layered composite deodorizing material, comprising the following steps:
[0040] Step 1: Catalyst layer preparation
[0041] The catalyst layer is composed of a titanium dioxide component that has a high decomposition power for malodorous substances and excellent particle dispersion stability.
[0042] 1. Copper mesh pretreatment: After immersing the 30-mesh copper mesh in acetone for cleaning, it is ultrasonically cleaned in deionized water for 5 minutes; then, the surface is etched with 10% wt dilute sulfuric acid for 30-40 seconds using a spraying method, rinsed with deionized water, and placed in a bag filled with N2 for later use.
[0043] 2. Catalyst preparation: Tetrabutyl titanate, ethanol, acetylacetone, water, and nitric acid were mixed in a molar ratio of 1:20:0.5:1:0.1. Acetylacetone was used as a chelating agent to inhibit the excessively rapid hydrolysis of tetrabutyl titanate.
[0044] 3. Coating: Immerse the copper mesh in the catalyst liquid at a rate of 10 cm / min and pull it up. Repeat 2-3 times to increase the coating thickness of the catalyst on the copper mesh surface.
[0045] 4. Drying and activation: Dry in a 60℃ oven for 10 min to remove organic solvents from the surface of the copper mesh. Then, in a N2 atmosphere, heat the mesh to 500℃ at 5℃ / min and maintain the temperature for 1 h to activate the surface catalyst. After cooling to room temperature in a N2 atmosphere at 2℃ / min, remove the mesh for later use.
[0046] Step 2: Preparation of the adsorption layer
[0047] Select a specific surface area of 1300-1600 m² 2 Microporous coconut shell activated carbon with a particle size of 0.18-0.25 mm (60-80 mesh) and an iodine value of 1000-1500 mg / g is prepared by impregnating mesoporous metal oxides with active components in equal volume using an ultrasonic method, and then uniformly mixing them with coconut shell activated carbon to obtain adsorption particles.
[0048] The preparation method of the active component is as follows: Select a component with a specific surface area of 800-1000 m². 2 Mesoporous manganese dioxide with a particle size of 100-150 nm is placed in an 85% ethanol solution, and the pH is adjusted to 4 with 30% nitric acid. The mixture is ultrasonically dispersed at a temperature of 45℃, and aminomethyltrimethoxysilane is added dropwise during the impregnation process. The mixture is then ultrasonically bathed in a water bath at 40 kHz for 90 min, followed by standing for 12 h. Finally, it is heated in a water bath at 60℃ with constant stirring until the liquid is completely eliminated, thus obtaining highly active manganese dioxide. The mass ratio of manganese dioxide to aminomethyltrimethoxysilane is 30:1.
[0049] Step 3: Preparation of composite filter materials
[0050] The copper mesh, the first hot melt adhesive layer, and the skeleton are laid flat on the worktable in sequence and then hot-pressed to fix them. A second hot melt adhesive layer is then laid on the surface, and adsorption particles are evenly spread to form an adsorption layer. A third hot melt adhesive layer is then laid on the adsorption layer and hot-pressed to fix it. Meltblown fabric is then stacked on the third hot melt adhesive layer. The materials stacked in the above sequence are pressed and shaped by hot pressing to obtain a composite filter material.
[0051] A desktop conveyor is installed below the copper mesh, and a high-voltage electrostatic powder spreader is installed above the copper mesh to ensure that the activated carbon can be evenly distributed in the skeleton layer. The powder amount of the high-voltage electrostatic powder spreader is adjustable within a range of 25%, and the conveying frequency of the desktop conveyor is set to 15Hz. This ensures the uniform distribution of carbon particles in the carbon layer while preventing carbon particles from falling off the fabric surface due to excessive amplitude, frequency, or time.
[0052] The bone material used is 45g / m³. 2 Polyester (PET) nonwoven fabric; the meltblown fabric layer uses 25g / m 2 Polypropylene (PP) meltblown nonwoven fabric; the first and third layers of hot melt adhesive mesh have a basis weight of 15 g / m². 2 The second layer uses a weight of 25g / m². 2 The copolyester (PES) hot melt adhesive mesh has a mesh melting temperature range of 80-120℃.
[0053] The amount of adsorbent particles laid is 200 g / m³. 2 .
[0054] The deodorizing material prepared above was cut into 200*200mm square filter media and applied to the purification test of ammonia / formaldehyde / methanethiol using a circulation method. The test temperature was 25℃ and the relative humidity was 50%. The gas removal efficiency under these conditions is shown in Table 1. The composite filter media achieved a 98% removal rate of ammonia within 30 minutes and a 99% removal rate of ammonia / formaldehyde / methanethiol within 60 minutes.
[0055] In this embodiment, the titanium dioxide in the catalytic layer can catalytically decompose malodorous molecules in the environment (such as ammonia, acetic acid, hydrogen sulfide, methanethiol, trimethylamine, formaldehyde, acetaldehyde, toluene, ethyl acetate, ethylene, benzene, acetone, pyridine, isovaleric acid, nonenal, and indole) into simple, odorless inorganic substances, which are then adsorbed by the activated carbon in the adsorption layer. The adsorption layer is mainly composed of activated carbon and mesoporous metal oxides. The mesoporous metal oxides have excellent deodorization performance while also removing formaldehyde: the amino groups on the surface of the metal oxides can react with formaldehyde in the environment to form alkali, and the basic groups on the surface can react with methanethiol to form stable disulfide bonds, thus simultaneously removing formaldehyde and odor. The products generated are adsorbed by the activated carbon, thereby achieving the effect of purifying the air. When gaseous pollutants pass through this filter material, odorous substances such as ammonia are converted into simple small molecule compounds under the catalysis of titanium dioxide. These compounds are then adsorbed by the activated carbon in the adsorption layer via mesoporous metal oxides. The mesoporous manganese dioxide reaction in the activated carbon layer is exothermic and reduces the energy required for the titanium dioxide catalytic reaction, thus promoting the forward catalytic reaction and increasing the removal efficiency of odorous substances such as ammonia.
[0056] Comparative Example 1
[0057] Compared to Example 1, the difference lies in that the titanium oxide on the surface after calcination in step one is collected, and then the powder is directly mixed with the adsorbent in step two, while the rest remains unchanged. As shown in Table 1, after the titanium oxide is directly mixed with activated carbon, the catalytic performance deteriorates due to the reduced number of light-contacting sites, resulting in a decrease in ammonia removal efficiency.
[0058] Comparative Example 2
[0059] Compared to Example 1, the difference lies in step two, where manganese dioxide is not activated and is directly mixed with activated carbon; the rest remains unchanged. In Comparative Example 2, compared to Example 1, the removal efficiency and adsorption capacity of formaldehyde and methanethiol both decreased significantly. This is because the unactivated manganese dioxide slowed down the capture of formaldehyde and methanethiol, resulting in a weakened adsorption efficiency.
[0060] Comparative Example 3
[0061] Compared to Example 1, the difference lies in that the activated carbon in step two is not loaded with active components, while the rest remains unchanged. In Comparative Example 3, the removal efficiency and adsorption capacity of formaldehyde and methanethiol both decreased significantly compared to Example 1. This is because the lack of loaded active components slows down the capture of formaldehyde and methanethiol, thus weakening the adsorption efficiency.
[0062] Comparative Example 4
[0063] The difference compared to Example 1 is that the activated carbon weight in step two is 100 g / m³. 2 Everything else remained unchanged. Compared with Example 1, the removal efficiency and adsorption capacity of formaldehyde and methanethiol in Comparative Example 4 decreased slightly. This was because the amount of activated carbon was reduced, which reduced its adsorption capacity for formaldehyde and methanethiol, thus resulting in a decrease in removal efficiency at 90 min.
[0064] Table 1. Odor Removal Efficiency of the Cyclic Method
[0065]
[0066] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A deodorizing material, characterized in that, It includes a catalyst layer, a first hot melt adhesive layer, a core material, a second hot melt adhesive layer, an adsorption layer, a third hot melt adhesive layer, and a meltblown fabric layer, which are stacked in sequence. The catalyst layer is loaded with titanium dioxide; the adsorption layer is obtained by spreading adsorption particles, which are a mixture of activated carbon and mesoporous metal oxides loaded with active components. The active component is highly active manganese dioxide; The preparation method of the highly active manganese dioxide is as follows: select a sample with a specific surface area of 800-1000 m². 2 / g of mesoporous manganese dioxide with a particle size of 100-150nm and a pore size range of 20-30nm was obtained by placing mesoporous manganese dioxide in an ethanol solution, adjusting the pH to acidic using a pH adjuster, dispersing it evenly, adding an amino-containing trimethoxysilane, and heating in a water bath until the solution completely disappeared, thus obtaining highly active manganese dioxide. The ethanol solution was 85% by volume; the pH adjuster was 30% by mass of nitric acid; the dispersion was performed by ultrasonic water bath dispersion at a frequency of 40 kHz and a temperature of 45 ℃; the mass ratio of mesoporous manganese dioxide to amino-containing trimethoxysilane was 30:1; and the water bath heating temperature was 60 ℃.
2. The deodorizing material according to claim 1, characterized in that, The catalyst layer is prepared by mixing tetrabutyl titanate, ethanol, acetylacetone, water and nitric acid to obtain an impregnation solution; then immersing a copper mesh in the impregnation solution, removing it, drying it, and calcining it to obtain the catalyst layer.
3. The deodorizing material according to claim 2, characterized in that, The molar ratio of tetrabutyl titanate, ethanol, acetylacetone, water, and nitric acid is 1: (10-40): (0.1-1.0): (0.5-2): (0.05-0.2).
4. The deodorizing material according to claim 2, characterized in that, During impregnation, the copper mesh is impregnated at a rate of at least 10 cm / min, and repeated multiple times to increase the thickness of the impregnation solution coating on the copper mesh; During drying, the drying temperature is 40-70℃, and the drying time is 5-15 minutes; During calcination, the calcination temperature is 450-600℃ and the calcination time is 0.5-1.5 h.
5. The deodorizing material according to claim 1, characterized in that, The adsorption particles are prepared by impregnating mesoporous metal oxide with an equal volume of active components using an ultrasonic method, and then mixing it evenly with activated carbon to obtain adsorption particles.
6. The deodorizing material according to claim 5, characterized in that, The mesoporous metal oxide is one or more of manganese, titanium, zinc, and copper; The activated carbon has a specific surface area of 1300-1600 m². 2 Microporous coconut shell activated carbon with a particle size of 0.18-0.25 mm and an iodine value of 1000-1500 mg / g; The mass ratio of the mesoporous metal oxide, active component and activated carbon is (25-35):1:(80-120).
7. The deodorizing material according to claim 1, characterized in that, The bone material has a weight of 40-50 g / m³. 2 Polyester nonwoven fabric; The basis weight of the first and third hot melt adhesive layers is 10-15 g / m². 2 ; The first hot melt adhesive layer and the third hot melt adhesive layer are hot melt adhesive meshes composed of one or more of polyolefins, copolyesters, and polyamides, and the melting range of the hot melt adhesive mesh is 80-120℃; The second hot melt adhesive layer has a basis weight of 18-25 g / m². 2 The copolyester hot melt adhesive mesh has a melting temperature range of 80-120℃.
8. A method for preparing a deodorizing material as described in any one of claims 1-7, characterized in that, Includes the following steps: The copper mesh, the first hot melt adhesive layer, and the skeleton are stacked on the workbench in sequence. After the first hot pressing to fix them, the second hot melt adhesive layer, the adsorption layer, and the third hot melt adhesive layer are stacked in sequence. After the second hot pressing to fix them, meltblown cloth is stacked on the third hot melt adhesive layer to obtain the deodorizing material. The adsorption layer is formed by uniformly spreading adsorption particles, with a particle spreading amount of 180-200 g / m³. 2 .
9. A method for preparing a deodorizing material according to claim 8, characterized in that, A desktop conveyor is installed below the copper mesh, with a transmission frequency set to 15-20Hz; A high-voltage electrostatic powder sprinkler is installed above the copper mesh, with the powder amount adjustable from 25% to 35%.
Citation Information
Patent Citations
Carbon clamping cloth for automobile air conditioner filter and preparation method of carbon clamping cloth
CN115888251A
Double-effect carbon clamping cloth with regeneration function for air purifier and preparation method of double-effect carbon clamping cloth
CN119186188A
Photocatalytic air-purifying net in multilayer structure and is making process
CN1288775A